Carbon ion mono-energetic and spread-out Bragg peak measurements using nanocomposite Fricke gel dosimeters with LET-independent response - Bayer, Viktoria; Vedelago, José; Dorsch, Stefan; Beyer, Cedric; Brons, Stephan; Johnen, Wibke; Biegger, Philipp; Weber, Ulrich; Runz, Armin; Karger, Christian (Radiation measurements, 2024)
This study investigates the LET-dependence of dose measurements performed with a nanocomposite Fricke gel (NC-FG) upon irradiation with carbon ion beams to address the problem of quenching of gel dosimeters in high-LET particle therapy. The preparation of the NC-FG in a simple gel preparation device was performed for atmospheric and anoxic environmental conditions and two different container materials. Irradiation was performed with carbon ion beams at energies of 133.39MeV/u or 194.87MeV/u, complemented by a modulated 10 mm carbon ion spread-out Bragg peak (SOBP) irradiation. The R1 profiles obtained from the MRI readout were compared to the treatment planning system and a 2D-ionisation chamber array measurement performed for the mono-energetic and SOBP irradiations, respectively. For different dose levels, no difference in the gel response was obtained for the 3D-printed plastic containers, while the glass vials exhibited a linear dose response. Additional use of the glove box changes produced similar results. For both the mono-energetic and the SOBP irradiation, a linear dose response without quenching was observed. For depths ranging up to the Bragg peak position, the mono-energetic profiles deviated by less than ± 15% from the planned dose distribution, excluding the lowest entrance surface dose (ESD). For the SOBP profiles, the deviation from the measured dose distribution was less than ± 10% for depths between 20 mm and 33 mm. This study presents a LET-independent measurement of mono-energetic carbon ion Bragg peaks and, for the first time, a LET-independent measurement of a carbon ion SOBP with the NC-FG prepared in a simple gel preparation device under atmospheric conditions. The NC-FG provides a possible solution for 3D dosimetry in carbon ion radiotherapy.
Gesehen am 26.03.2025